Managing pessimistic expectations and fiscal policy - Anastasios G. Karantounias (Federal Reserve Bank of Atlanta, 2012)
This paper studies the design of optimal fiscal policy when a government that fully trusts the probability model of government expenditures faces a fearful public that forms pessimistic expectations. We identify two forces that shape our results. On the one hand, the government has an incentive to concentrate tax distortions on events that it considers unlikely relative to the pessimistic public. On the other hand, the endogeneity of the public's expectations gives rise to a novel motive for expectation management that aims towards the manipulation of equilibrium prices of government debt in a favorable way. These motives typically act in opposite directions and induce persistence to the optimal allocation and the tax rate.
Keywords: D80; E62; H21; H63; 330; fiscal policy; misspecification; robustness; debt; martingale; taxes